Imperial archipelago : representation and rule in the insular territories under U.S. dominion after 1898 - Thompson, Lanny (Writing past colonialism series., 2010)
Provides a comparative study of the symbolic representations, both textual and photographic, of Cuba, Guam, Hawaii, the Philippines, and Puerto Rico that appeared in popular and official publications in the aftermath of the Spanish-American War of 1898. It examines the connections between these representations and the forms of rule established by the US in each at the turn of the century.